THE DISCIPLINE IMPROVEMENT OF TEACHERS' ARRIVAL USING SENTURI MODEL IN ELEMENTARY SCHOOL - Nurdin, Ali; Sugiana, Aat (JPSD (Jurnal Pendidikan Sekolah Dasar), 2019)
Abstract. The School Action Research (PTS) was conducted to discuss the application of the “Senturi” model towards the discipline of teachers’ arrival. Senturi stands for "Time Presence for Self-Control". At the beginning, the average arrival of teachers at 07.25 or only 8% did not came late, the rest 92% still come late. Of course this condition is very worrying. From this problem, the researcher tries to solve the problem by applying the Senturi Attendance List, which is the attendance list by calculating the teacher's arrival time on the card and the format provided. This type of research is quantitative and qualitative experimental research. The base population is all Teachers / Staff in Group V as many as 82 people. And the sample is all teachers / staff of Curug Public Elementary School as many as 13 respondents. By determining the sample approved in the opinion of Arikunto (1992: 107) namely "if the object of research is greater than 100 respondents taken 20%-30%. But if less than 100 respondents, the sample was taken entirely”. This research concludes "The application of the "Senturi Attendance List” has a significant influence on the disciplines improvement of teachers’ arrival to school". This is supported by data on the average improvement of teachers' arrival to schools from 07.25 to 07:00, and those who arrived late starting at 92% dropped significantly to only 8%.Keywords: time discipline, senturi model